SEG Technical Program Expanded Abstracts 2010 2010
DOI: 10.1190/1.3513386
|View full text |Cite
|
Sign up to set email alerts
|

Measuring gas shale permeability tensor in the lab scale

Abstract: Permeability tensor measurements for three different gas shale samples were done using quasi-steady flow technique in specially designed apparatus in which confining pressure, upstream pore pressure, downstream pore pressure and temperature are independently controlled. The initial pressure difference between upstream and downstream changes only after the pressure pulse passes across the whole sample. Using the quasi-steady flow technique gives the ability to measure axial permeability of three different orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Since fractured media has strong stress sensitivity in permeability, research on permeability tensor formulation and stress sensitivity has been reported in the literature. Metwally et al (2010) studied permeability tensor of shale by laboratory test method, and found the relationship between anisotropy ratio and the effective pressure. Chen et al (1998) studied stress changes of an anisotropic reservoir, and found the evolution of reservoir stress anisotropy would be influenced by the trend of permeability anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Since fractured media has strong stress sensitivity in permeability, research on permeability tensor formulation and stress sensitivity has been reported in the literature. Metwally et al (2010) studied permeability tensor of shale by laboratory test method, and found the relationship between anisotropy ratio and the effective pressure. Chen et al (1998) studied stress changes of an anisotropic reservoir, and found the evolution of reservoir stress anisotropy would be influenced by the trend of permeability anisotropy.…”
Section: Introductionmentioning
confidence: 99%